Cryptanalysis of Curl-P and Other Attacks on the IOTA Cryptocurrency - Ethan Heilman; Neha Narula; Garrett Tanzer; James Lovejoy; Michael Colavita; Madars Virza; Tadge Dryja (IACR Transactions on Symmetric Cryptology, 2020)
We present attacks on the cryptography formerly used in the IOTA blockchain, including under certain conditions the ability to forge signatures. We developed practical attacks on IOTA’s cryptographic hash function Curl-P-27, allowing us to quickly generate short colliding messages. These collisions work even for messages of the same length. Exploiting these weaknesses in Curl-P-27, we broke the EUCMA security of the former IOTA Signature Scheme (ISS). Finally, we show that in a chosen-message setting we could forge signatures and multi-signatures of valid spending transactions (called bundles in IOTA).